A new species of Frullania subg. Frullania (Marchantiophyta) from the Brazilian Amazon - Lima, Eliene; Ilkiu-Borges, Anna Luiza; Gradstein, S. Robbert (Phytotaxa, 2020)
Frullania subg. Frullania (= subg. Thyopsiella) is a little-known group of liverworts in the Neotropics, being represented by only two species. Both are members of the subsect. Microphylla characterized by very small, dioicous plants, ocellate leaves, caducous leaf lobes and very small, distant underleaves. Here we describe and illustrate a third neotropical species in this group, F. amazonica sp. nov., from the Amazon region of Brazil. The new species is readily distinguished from its two allies in the elongate median leaf cells, the very narrow, oblong underleaves with rounded apices and the strongly toothed female bracts and bracteoles. The new name F. section Microphyllae (R.M.Schust.) comb. nov. is proposed and a key is provided to the neotropical members of this section.